2019
DOI: 10.1039/c8gc03290d
|View full text |Cite
|
Sign up to set email alerts
|

Defining lignin nanoparticle properties through tailored lignin reactivity by sequential organosolv fragmentation approach (SOFA)

Abstract: Sequential organosolv fragmentation approach (SOFA) enhances the self-assembling process of high-quality lignin nanoparticles (LNPs) by tailoring the lignin chemistry in biorefineries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 64 publications
1
65
0
Order By: Relevance
“…These intermediate steps add substantial energy and chemical consumption and it would be ideal if the black liquor could be used as such as raw material or alternatively if the lignin particles could be produced directly from biorefinery residues. It has been shown that sequentially isolated lignin fractions from the same feedstock differ in their structural features, 185,186 and that these fractions lead to different properties of the spherical lignin particles. 186 However, there is a lack of correlation of particle properties with lignin properties from various sources and after different extent of purification.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These intermediate steps add substantial energy and chemical consumption and it would be ideal if the black liquor could be used as such as raw material or alternatively if the lignin particles could be produced directly from biorefinery residues. It has been shown that sequentially isolated lignin fractions from the same feedstock differ in their structural features, 185,186 and that these fractions lead to different properties of the spherical lignin particles. 186 However, there is a lack of correlation of particle properties with lignin properties from various sources and after different extent of purification.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…It has been shown that sequentially isolated lignin fractions from the same feedstock differ in their structural features, 185,186 and that these fractions lead to different properties of the spherical lignin particles. 186 However, there is a lack of correlation of particle properties with lignin properties from various sources and after different extent of purification. When precipitated from spent pulping liquors, lignin often contains impurities such as polysaccharides, rosin acids, and other extractives from wood.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…A sensor material containing hierarchical zinc oxide (ZnO) nanorods grown in the presence of lignin was used for sensing of ammonia gas based on the semiconducting properties of ZnO. [108] However, ZnO nanostructures have been known for decades for gas sensing applications. [109,110]…”
Section: Sensors For Metal Ions and Hydrogen Peroxidementioning
confidence: 99%
“…This phenomenon may attribute to the lignin recombination and condensation that happened in the acidic environment under mild conditions (TH22) after the depolymerization [31]. It is worth noting that it is easier for high content of G-type lignin or low S/G lignin to form small size nanoparticles [15]. Therefore, in order to achieve the preparation of lignin nanoparticles with smaller particle size, the reaction solvent must have the ability to dissolve more Gtype lignin.…”
Section: D-hsqc-nmr Analysismentioning
confidence: 99%
“…For example, the uniform colloidal spheres were prepared via self-assembly with alkali lignin recovered from the pulping black liquor and chemically modified by acetylating [14]. Recently, lignin nanoparticles directly prepared with lignin produced from lignocellulose pretreatment were proposed [15,16], which not only avoids lignin modification, but also realizes the utilization of waste lignin. However, the preparation of lignin nanoparticles and enzymatic hydrolysis of carbohydrates from lignocellulosic biomass are different and independent processes, therefore, the lignin with suitable structure for excellent colloidal spheres formation is usually obtained at the expense of sugar yield, due to the accessibility of carbohydrate to enzymes resulted from the destruction of lignin in the lignocellulosic biomass is not good enough.…”
Section: Introductionmentioning
confidence: 99%